THE MYSTICAL IDEAS PUT FORWARD BY ALISHER NAVOI IN HIS WORK "ARBA'IN" ("FORTY HADITHS") (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The articie analyzes the mystical ideas put forward by Alisher Navoi in his work "Arba'in" ("Forty Hadiths")